Perbaikan Keragaan Bibit Jeruk Pamelo ‘Nambangan’ dengan Strangulasi - Wahyu Fikrinda; Slamet Susanto (Indonesian Society for Horticulture / Department of Agronomy and Horticulture, 2017)
ABSTRACTPummelo seedling has branches that grow irregularly, stright up, and has less branch. Attempt should be done to stimulate the formation of new branches. The objective of the research was to study the influence of single and double strangulation for stimulation of vegetative growth in order to improve canopy architecture of pummelo seedling. The experiment was conducted from March to September 2011 in green house of Cikabayan Experimental Station IPB, Bogor. Biochemical analysis was done in Laboratory of BALITRO, Bogor and Post-Harvest Laboratory, IPB. The experiment was conducted in Completely Randomized Block Design one factor consisting of 5 treatment: control, single strangulation, double strangulation with distance between wire 5 cm, 10 cm and 15 cm. The experiment consisted of 5 replicates. There were 25 experimental units. Each experimental unit contained 2 plants and total plants were 50 plants. Strangulation treatment was done in May 19th and wires were removed in August 10th 2011. The results of this research showed that single and double strangulation improved numbers of branch, the lenghth of shoots per plant, numbers of leaf, numbers of scion diameter, volume of canopies andstarch content in leaf. Double strangulation with distance between 2 wires 15 cm had open canopy and the highest volume of canopies with good canopy appearance at 19 week after application. Strangulation did not cause permanent damage of the sytem tissue and only took two months to recover.Key words: branch, canopy appearance, starch, volume of canopiesABSTRAKJeruk pamelo memiliki cabang yang tumbuh tidak beraturan, cenderung lurus ke atas dan bercabang sedikit. Upaya untuk merangsang pembentukan cabang baru adalah dengan strangulasi. Tujuan penelitian ini adalah mempelajari pengaruh strangulasi tunggal dan ganda dalam merangsang pertumbuhan vegetatif untuk perbaikan keragaan bibit jeruk pamelo. Percobaan dilaksanakan bulan Maret sampai September 2011 di greenhouse Kebun Percobaan Cikabayan IPB, Bogor. Analisis biokimia dilakukan di Laboratorium Balai Penelitian Tanaman Obat dan Aromatik (BALITRO), Bogor dan Laboratorium Pasca Panen, IPB. Percobaan menggunakan Rancangan Acak Lengkap (RAL) satu faktor sebanyak 5 perlakuan yaitu tanpa strangulasi, strangulasi tunggal dengan ketinggian 5 cm dari mata tempel, strangulasi ganda dengan jarak antar kawat 5 cm, 10 cm dan 15 cm. Percobaan terdiri atas 5 ulangan dan setiap satu satuan percobaan terdiri atas 2 tanaman sehingga total terdapat 50 tanaman. Aplikasi strangulasi dilaksanakan pada 19 Mei dan kawat dilepas pada 10 Agustus 2011. Hasil penelitian menunjukkan strangulasi tunggal dangan meningkatkan jumlah cabang, panjang cabang per tanaman, jumlah daun, diameter batang, volume tajuk, dan kandungan karbohidrat daun. Aplikasi strangulasi ganda memiliki tajuk terbuka dan volume tajuk terbesar dengan keragaan kanopi yang baik pada 19 minggu setelah perlakuan. Strangulasi tidak memberikan efek merusak secara permanen dan waktu pulihnya hanya dua bulanpada jaringan batang tanaman.Kata kunci: cabang, karbohidrat, keragaan tajuk, volume kanopi